Analisis Kesiapsiagaan Masyarakat dalam Menanggulangi Bencana Alam di Indonesia (Studi pada Bencana Alam di Sumatera Utara) - Meili, Maya; Sembiring, Zamalludin (Al-DYAS, 2025)
This research is motivated by concerns and also the number of natural disasters in Indonesia, including the North Sumatra region which is prone to various types of disasters such as earthquakes, floods, and volcanic eruptions. Community preparedness plays an important role in efforts to mitigate disaster risk and reduce its impact. This study aims to analyze the level of community preparedness in dealing with natural disasters in several vulnerable areas in North Sumatra and the factors that affect them. The method used is a qualitative descriptive approach with data collection through interviews, observations, and documentation, with analysis using the theory of B Miles and Huberman. The results show that the level of community preparedness is in the category of "quite prepared", but there are still weaknesses in terms of technical knowledge about emergency response, the use of evacuation routes, and the lack of regular training from relevant institutions. Factors such as education, previous experience of disasters, and access to information have been proven to have a significant effect on community preparedness. Therefore, efforts to improve structured and community-based disaster education are needed to build community resilience to disasters in a sustainable manner. The implication is to provide information that the community is ready for disasters, but some are not, therefore the government has a role to always be ready so that the community is able to overcome natural disaster problems, especially in disaster-prone areas.